(untitled) (Experimental biology, 2023)
A considerable amount of published sources contain incomplete data, as significant knowledge about the diversity of living organisms has been accumulated in museum collections and monographic publications. Data on the findings of land mollusks in the Northern Tien Shan taken from the literature were used. Based on these incomplete data, the distribution of terrestrial mollusks was reconstructed in the whole region. As a result species richness of gastropods in the Northern Tien Shan is not dependent on geographic locality. The study found significant similarities in the fauna of different mountain ridges, with spatial proximity being a significant factor in determining faunal similarity. The difference in the malacofauna between Ile and Kungey Alatau is likely due to the uneven representation of Kungey Alatau in previous studies. The data reconstruction method performed in the study proved to be a simple and quick approach for preliminary estimating faunistic diversity. While this method has some limitations, they can be avoided by incorporating environmental data.